Local and global pareto dominance in multi-populations evolution applied to optimization of composites - C. A. C. António (2012)
The goal of the proposed multi-objective optimization algorithm is the search of the Pareto-optimal front keeping good population diversity using a hierarchical genetic algorithm with co-evolution of multi-populations. A self-adaptive genetic search incorporating Pareto dominance and elitism is presented. Two concepts of dominance are used: the first one denoted by local non-dominance is performed at the isolation stage of populations and the second one called global non-dominance is performed on the age structured population. The age structured population is used to store the ranked solutions with the aim of obtaining the Pareto front after the evolutionary process. The application to composite structures with the compromise between minimum strain energy and minimum weight is presented. (c) Civil-Comp Press, 2012.